An analysis of hospital cleaning staff's attitudes and conduct regarding hand hygiene and cleaning. Issue 2 (2nd April 2016) - Pirincci, Edibe; Altun, Bengu
Abstract : Objective . The aim of this study was to analyze the attitudes and conduct of hospital cleaning staff regarding cleaning and hand hygiene. Methods . In May and June 2014, the cleaning staff of Elazig Training and Research Hospital participated in this descriptive research. Data was collected by a survey prepared by the researchers. The SPSS program was used to analyze the data. Results . Of the participants, 70.3% of them were male and their mean age was 38.69 ± 6.61. The percentage of those hand washing before starting work was 29.8% for primary school graduates or those with lower education. For those with higher levels of education, the percentage was 68.2% ( p < 0.001). The percentage of participants who wash their hands after work was 54.3% for primary school graduates and those with lower levels of education. For those with a higher level of education, the percentage was 84.1% ( p < 0.001). The participants' use of personal protective equipment during work was that 97.8% of them used gloves, 39.9% bonnets and 56.5% medical masks. Conclusions . The attitudes and conduct of the cleaning staff are not sufficiently hygienic. These employees need training before and throughout their employment.